Keeping Teachers Up-to-date is essential to reach and maintain a High Quality University Education - Leonor Aguilar-Santelises; María Teresa Corona Ortega; Margarita Cruz-Millán; Antonia Guillermina Rojas-Fernández; Miguel Aguilar-Santelises; Araceli García del Valle (Multidisciplinary Journal for Education, Social and Technological Sciences)
A multidisciplinary group of teachers and scientists from the Faculty for Higher Education (FES) Zaragoza from the National Autonomous University of Mexico (UNAM) has been working during several years, forwarding and testing strategies for the continuous improvement of biochemistry theoretical and experimental teaching, within the various levels from the chemistry, pharmacy and biology (QFB) curricula at our University. To provide our teachers with modern teaching abilities to satisfy current national demands of high-level education is our top priority. Therefore, we offer various activities to promote their continuous scientific and didactic updating. We also encourage self-awareness on the strong need for continuous adaptation and utilization of information and communication technologies (ICT) that have become very popular among young generations. Teaching is not an isolated discipline. On the contrary, teaching is intimately related with social and economical circumstances. Teachers and students must be aware of their social environment, studying and applying modern techniques, improving their scientific capabilities, which are all necessary to approach national problems with an accurate utilization of national resources. Research and development have to be linked to the best teaching techniques that stimulate teachers and scientists to grow as educators and experimenters continuously looking for feedback from their students and colleagues. Our scientific meetings and advanced and basic courses on scientific topics and teaching techniques have contributed not only to promote individual teaching and scientific capabilities but also to update the study plans from the QFB curricula at our University.